Progress of Wearable and Flexible Electrochemical Biosensors With the Aid of Conductive Nanomaterials - Raza, Tahir; Qu, Lijun; Khokhar, Waquar Ahmed; Andrews, Boakye; Ali, Afzal; Tian, Mingwei (Frontiers in Bioengineering and Biotechnology, 2021)
Conductive nanomaterials have recently gained a lot of interest due to their excellent physical, chemical, and electrical properties, as well as their numerous nanoscale morphologies, which enable them to be fabricated into a wide range of modern chemical and biological sensors. This study focuses mainly on current applications based on conductive nanostructured materials, because they are the key elements in the preparation of wearable electrochemical sensors, biosensors, including immunosensors and DNA biosensors. Conductive nanomaterials such as carbon (Carbon Nanotubes, Graphene), metals and conductive polymers which provide large effective surface area, fast electron transfer rate and high electrical conductivity are summarized in detail. Conductive polymer nanocomposites in combination with carbon and metal nanoparticles have also been addressed in order to increase sensor performance. As a conclusion, a section on current challenges and opportunities in this growing field is forecasted at the end.